Ökonomismus zum Wohlfühlen: Gøsta Esping-Andersen und die neue Architektur des Sozialstaats - Lessenich, Stephan (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2004)
Gøsta Esping-Andersen is the top star not only of contemporary comparative welfare state research but of European social democrats struggling for welfare state reform as well. The article discusses Esping-Andersen’s vision of a „new welfare state“ and points out why finally even German social democracy discovered the sex appeal of his plea for „investing in women and children“.